EDUKASI PEMANFAATAN TANAMAN KELOR (Moringa oleifera L.) SEBAGAI PENCEGAHAN PENYAKIT DEGENERATIF DAN PEMERIKSAAN KESEHATAN GRATIS BAGI LANSIA DI DESA SUNGAI RANGAS - Nurul Amelia; Esty Restiana Rusida; Didik Rio Pambudi; Rahmiati Rahmiati (Jurnal SADEWA, 2024)
Many elderly people experience degenerative diseases, such as hypertension and diabetes mellitus. Degenerative disease handlers are currently starting to use herbs such as the Moringa plant as an alternative. The aim of community service is to educate the public so that they can use Moringa as an alternative to treat degenerative diseases. The method used was a mini talk show for young people in RT 01 Sungai Rangas Village. The results obtained by the mini talk show were attended by 33 people, 26 of whom were community members. The conclusion of this service activity is that it can contribute to the community with free health checks and education on the use of Moringa plants.